Effect of lipid matrix on repaglinide-loaded solid lipid nanoparticles for oral delivery - Rawat M.K.; Jain A.; Mishra A.; Muthu M.S.; Singh S. (My University, 2025)
Aim: To study the effect of different types of lipid on the entrapment efficiency (EE) and physical stability of repaglinide (RG)-loaded solid lipid nanoparticles (SLNs). RG-loaded SLNs were prepared by modified solvent injection method using stearic acid (RSA), glycerol monosteratae (RGM), glyceryl behenate (RGB) and tristearin (RTS). Poloxamer F68 was used as a stabilizer. Results: SLNs were characterized by particle size, zeta-potential, EE, in vitro release, solid-state properties (differential scanning calorimetry, transmission electron microscopy and electron diffraction) and stability at 30°C/65% relative humidity for 3 months. The mean particle size and zeta-potential of RG-loaded SLNs prepared with different lipids in varying concentrations ranged from 150 to 355 nm and -21.04 ± 3.10 to -30.54 ± 2.76 mV, respectively. Conclusion: EE was found to vary with lipids in the following order: RSA < RGM < RGB < RTS. Tristearin-prepared SLNs showed a significant prolonged drug release up to 24 h. Differential scanning calorimetry and electron diffraction microphotograph results indicated that RG entrapped in the SLNs existed in an amorphous or molecular state. SLNs prepared with stearic acid, glycerol monostearate and glyceryl behenate after storage showed significant increases in particle size, polydispersity index and EE. The SLNs prepared with tristearin were stable. © 2010 Future Science Ltd.